Commercialization of meat products at street market in the city of Fortaleza (CE): evaluation of conformities according to legislation (Research, Society and Development, 2020)
This work evaluated the hygiene conditions of meat products sold in street markets in Fortaleza (CE). The chosen fairs can be considered medium-sized and take place in a fixed place. For the evaluation, a checklist adapted from Ordinance N° 31/ 2005, was used the following criteria: handlers, product packaging, water supply, handling waste, instruments and utensils used, cleaning the environment, presence of objects in disuse, waste management and the origin and quality of raw material used. To compose the profile of the permissionaires in the stalls, education and time working as marketer was included in the checklist. After obtaining the data, the fair stores were classified into groups, according to the percentage of conformities. The permissionaires education level was similar between the evaluated fairs. Most were characterized without schooling or did not want to answer, 62% and 66% at fairs 1 and 2, respectively. Time as a seller of meat products varied from 2 to 25 years. Only 12 stalls agreed to participate; being four for each category of meat (beef, poultry and fish). According to Ordinance N° 31/05, the fairs were classified in group 03, as they presented a lower percentage of conformities than 50%. It was found that the fairs evaluated operate in conditions that compromises the quality of the commercialized meat products and can put  consumers' health at risk. It is suggested that there be greater inspection by competent organizations, health promotion campaigns to minimize risks and promote awareness among marketers and consumers.